Description of Patient Opinion About Covid-19 Vaccine at Al Mulk Hospital, Sukabumi City Year 2021 - Fety Lies Priyanti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
COVID-19 has been declared a world pandemic by WHO (WHO, 2020). Nationally, through the Decree of the Head of the National Disaster Management Agency Number 9A of 2020 which was updated through Decree number 13 A of 2020, the Status of Certain Disaster Emergency Conditions for Disease Outbreak due to Corona Virus in Indonesia has been determined as well as Presidential Decree Number 11 of 2020 concerning the Determination of Public Health Emergencies for COVID-19, then updated by Presidential Decree No. 12/2020 concerning the Designation of Non-Natural Disaster for the Spread of COVID-19 as a National Disaster. Vaccination for COVID-19 is an important part of efforts to deal with the COVID-19 pandemic that is comprehensive and integrated covering aspects of prevention by implementing health protocols: maintaining distance, washing hands with soap and wearing masks (3M), COVID-19 vaccination, and 3T (Tes, Search, Follow Up). Therefore, the authors wish to see the conditions or opinions of the public about this Covid 19 vaccination, the research was carried out simply by using a sample of people who visited Al Mulk Hospital. People who come to the hospital are made as respondents about the vaccination problem. The results of the level of public opinion about COVID-19 at Al Mulk Regional Hospital were known by using a questionnaire that obtained good public opinion results. Most of the respondents are aware of the government's vaccine program and there are still many respondents who are still doubtful that vaccines will be targeted for education about vaccines.